Perception and assessments on home school tasks in the Primary Education stage: the vision of teachers and students - Vázquez Toledo, Sandra; Cosculluela, Cecilia Latorre; Sánchez, Verónica Sierra; Orús, Marta Liesa (Avances en Supervisión Educativa, 2019)
The present study aims to show the perceptions that teachers and students report regarding homework which is assigned to students from the school. Driven by the current theme, a descriptive study has been carried out in which the questionnaire has been the main instrument of data collection. The sample consisted of 55 teachers and 35 students from Primary Education stage. The data obtained indicate some discrepancies in the importance that teachers and students give to these tasks, especially with regard to the perception of their usefulness and its implication for learning. As conclusions, the need for a reorientation in the type of homework is emphasized, so that it adapts to the individuality of each one to achieve a balance between academic, family and leisure activities.